PENGARUH BENTUK LATIHAN DAN JENIS TEKS TERHADAP HASIL BELAJAR MEMBACA PEMAHAMAN SISWA SLTP - Sunarti Sunarti (Jurnal Kependidikan, 2005)
Abstract The objective of this research was to find out the  influence of the form of exercises and the type of text on the students’ achievement in reading for comprehension. The exercises consisted of answering questions and making a summary, and the texts were narrative, descriptive, expository, and argumentative. Using the 2 x 4 factorial designs, the research was conducted in a State Junior High School. The results of the analysis indicated that: (1) the form of exercise influenced the students’ achievement in reading descriptive and expository tests. The mean of scores on reading comprehension on descriptive and expository texts achieved by the students trained using summary- making exercise was higher than the mean of scores on reading comprehension test of the students trained using question-answering practice. The form of the exercise did not influence the students’ achievement in reading narrative and argumentative texts. Keywords: reading exercise, types of text